2014
DOI: 10.1001/jamasurg.2013.5009
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status and Health Care Costs in the Perioperative Period

Abstract: IMPORTANCE Cigarette smoking adds an estimated $100 billion in annual incremental direct health care costs nationwide. Cigarette smoking increases complication risk in surgical patients, but the potential effects of smoking status on perioperative health care costs are unclear. OBJECTIVE To test the hypothesis that current and former smoking at the time of admission for inpatient surgery, compared with never smoking, are independently associated with higher incremental health care costs for the surgical epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…This study found that the total cost of hospitalization for the current and former smoker categories were respectively 65% and 26% higher in unadjusted model and 35% and 24% in the adjusted model higher than for the never smoker category of patients. These findings are in line with other studies that have reported increased costs in current and former smoker patients compared to never smokers ( 2 , 11 , 14 , 15 , 22 ). A study in Germany reported a positive association between history of smoking, and direct and indirect costs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that the total cost of hospitalization for the current and former smoker categories were respectively 65% and 26% higher in unadjusted model and 35% and 24% in the adjusted model higher than for the never smoker category of patients. These findings are in line with other studies that have reported increased costs in current and former smoker patients compared to never smokers ( 2 , 11 , 14 , 15 , 22 ). A study in Germany reported a positive association between history of smoking, and direct and indirect costs.…”
Section: Discussionsupporting
confidence: 93%
“…The monthly cost of hospitalization for current smokers was $400 higher than the costs for never smokers. However, the cost for former smokers was $273 higher than the costs for never smokers ( 14 ). In our study, the difference in cost of hospitalization between current and never smokers was 17.9 million IR, whereas the difference between former smokers and never smokers was 7.2 million IR.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we cannot conclude that the presence of respiratory diseases interfered with the spirometric results, since the number of patients submitted to the test who presented respiratory diseases was too small and insufficient for an accurate statement. associated with a decrease in the secretion transport, an increase in mucus secretion, and in airway narrowing [26][27][28] .…”
Section: Resultsmentioning
confidence: 99%
“…Increasing relative priority to provide treatment (IIID3) can be challenging in the face of the many other competing priorities. Discussion of evidence that smokers incur additional expenses compared with non-smokers can be used to bolster economic arguments, 17 as can the fact that tobacco treatment is among the most cost effective medical interventions available. [100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] Outer setting factors that provide incentives to treat should also be identified and invoked.…”
Section: Decision Aidsmentioning
confidence: 99%
“…It will discuss the prevalence and consequences of perioperative smoking; the principles of tobacco use treatment; the benefits of treating tobacco use in the surgical patient; the current state of implementation of tobacco treatment in clinical practice, including never smokers, current smokers incurred $400 (95% confidence interval $131 to $669) monthly additional medical costs over the first year after surgery. 17 When extrapolated to the US population, smoking results in approximately $10bn (£7.8bn; €8.8bn) annual excess postoperative costs. The risks of smoking extend beyond the smoker to people exposed to secondhand smoke; children and adults undergoing surgery who are exposed preoperatively to secondhand smoke have an increased risk of respiratory complications.…”
Section: Introductionmentioning
confidence: 99%